IstikhdÄm al-Wasilah al-Syamâ€™iyyah al-Bashiriyyah li Tarqiyah Maharah Qiraâ€™ah al-AkhbÄr al-â€˜Arabiyyah - Wahyudi, Dedi; Sanah, Siti; Ardiansyah, Ade Arip; Rizkina, Qisti Rafelita (Institut Agama Islam Negeri Curup, 2023)
This study aimed to evaluate community members' skills and comprehension in reading Arabic news before and after they used audio-visual media. The theoretical underpinning of this study is the idea that exposure to audio-visual materials will enhance one's news reading skills. The researchers' theory states that people interested in reading the news through audio-visual media have improved their news-reading skills. The method used in this research was a quasi-experimental method with a one-group design based on pre-test and post-test. The population in this study covered all members of the news reading community, totalling 20 students at UIN Sunan Gunung Djati Bandung. This research used quantitative data analyses of pre-test and post-test results using the Lilioforce equation. One of the present studyâ€™s results showcased that prior to employing the audio-visual media, the members of Arabic Language Teaching Division's news-reading mission had a poor level, as seen by the average score of 68.3. Their grade after utilizing it was good, as evidenced by the average score of 87.2. According to the interpretation criterion, the result of (N-D) was 0.60 or 60% in a moderate classification. Therefore, these results indicated that the audio-visual method effectively improved news-reading skills. This study suggests futureâ€™s research to assess the other foreign language proficiency in greater detail using a wider range of research techniques.Â